A placebo-controlled investigation of synaesthesia-like experiences under LSD. (29th July 2016) - Terhune, Devin B.; Luke, David P.; Kaelen, Mendel; Bolstridge, Mark; Feilding, Amanda; Nutt, David; Carhart-Harris, Robin; Ward, Jamie
Abstract: The induction of synaesthesia in non-synaesthetes has the potential to illuminate the mechanisms that contribute to the development of this condition and the shaping of its phenomenology. Previous research suggests that lysergic acid diethylamide (LSD) reliably induces synaesthesia-like experiences in non-synaesthetes. However, these studies suffer from a number of methodological limitations including lack of a placebo control and the absence of rigorous measures used to test established criteria for genuine synaesthesia. Here we report a pilot study that aimed to circumvent these limitations. We conducted a within-groups placebo-controlled investigation of the impact of LSD on colour experiences in response to standardized graphemes and sounds and the consistency and specificity of grapheme- and sound-colour associations. Participants reported more spontaneous synaesthesia-like experiences under LSD, relative to placebo, but did not differ across conditions in colour experiences in response to inducers, consistency of stimulus-colour associations, or in inducer specificity. Further analyses suggest that individual differences in a number of these effects were associated with the propensity to experience states of absorption in one's daily life. Although preliminary, the present study suggests that LSD-induced synaesthesia-like experiences do not exhibit consistency or inducer-specificity and thus do not meet two widely established criteria for genuine synaesthesia. Highlights: LSD-induced synaesthesia-like experiences were studied in a placebo-controlled study. Participants reported more spontaneous synaesthesia-like experiences under LSD. LSD-induced experiences did not meet two established criteria for synaesthesia. Some features of LSD-induced experiences were related to the trait of absorption.